PENGARUH ARANSI KELAS DALAM PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN PEMAHAMAN SAINS DAN KETERAMPILAN SOSIAL - Fadhila Cendra Irianti; Diana Endah Handayani; Iin Purnamasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the difficulty experienced by students in understanding the material, which results in low learning outcomes, limited communication skills, and inability to solve problems collaboratively, indicating that their social skills have not yet developed optimally. In addition, the seating arrangement does not allow students to actively engage in the learning process. This research is quantitative using a pre-experimental design with a one-group pretest posttest design. The research population was all fourth-grade students of SD Negeri Rejosari 02, with a sample of 23 students selected, using a non- probability sampling technique with saturated sampling. The data were collected through interviews, tests, documentation, and observation. Based on the data analysis, the average pretest score was 56.522 and the average posttest score was 89.565. The t-test hypothesis test resulted in tcount = 8.768 with df = n1 + n2 – 1 = 23 + 23 – 1 = 45, and at a 5% significance level, the ttable value was 2.014. Because tcount > ttable namely 8.768 > 2.014, ?0 was rejected. This means there was a significant difference between the pretest and pos-test average learning outcomes. The n-gain calculation was 0.749, which falls into the high category, indicates that classroom arrangement in project-based learning effectively improves students scientific understanding. In addition, students social skills such as their ability to cooperate, engage in discussions, and solve problems also developed positively. Thus, classroom arrangement in project-based learning has a positive effect on improving science understanding and social skills.